When does digital matter? Analysing customers' preference for digital processes. (11th June 2021) - Graupner, Enrico; Trenz, Manuel; Maedche, Alexander
Projected growth rates and potential cost savings shift the focus of companies to their digital channels. However, customers do not want to conduct all service processes digitally, resulting in customers regularly switching between physical and digital channels. This paper examines how service-specific requirements lead to digital channel use and how the impact of those inhibitors and drivers varies across search and purchase stages of the service process. The paper builds upon process virtualisation theory and focuses on IT-based virtualisation, commonly referred to as digitisation. An empirical study with 798 retail banking customers confirms that preferences for service digitisation are not only shaped by inhibiting factors, but also by drivers for digitisation. Interestingly, the results reveal that customers can require diverse levels of digitisation for the search and purchase stage. The model provides an explanation for why digitised stages of a service process may be accepted or rejected by the customer.